Computational and Experimental Investigations of a Sound Pressure Level Distribution at the Outlet of the Spiral Duct - ŁAPKA, Wojciech; CEMPEL, Czesław (Archives of Acoustics, 2008)
This paper describes a computational and experimental investigations of a sound pressurelevel distribution at the outlet of the spiral duct. A finite element method was used tocompute a three-dimensional numerical models in a COMSOL Multiphysics computer application.Both, numerical and experimental models of the spiral duct were placed solidly ina circular duct and they were approximately of the same size with a mandrel placed axially.For experimental investigations of sound pressure distribution, the measurements were carriedout in a square plane, about 16 cm per 16 cm, perpendicular to the mandrel’s axis and placedat a distance of 2.5 cm from the outlet of the spiral duct. The nearest surroundings of theoutlet of the spiral duct was covered by an absorptive material. As the computational outletsurroundings was set up an empty air volume with a boundary conditions of a characteristicimpedance of the air. This gives the same conditions as an anechoic chamber. It is presentedthat computational model is very similar to experimental one. Specific sound pressure leveldistribution at the outlet of the spiral duct is presented as computed and measured experimentally.This comparison shows good agreement between experimental and numerical resultsand it reveals great potential for applications as a newly discovered acoustic band stop filter –the spiral duct.